EMOTIONAL DEPENDENCE AND NARCISSISM: RELATIONS WITH SOCIAL BEHAVIORS AND GENDER INEQUALITY - Araújo da Silva, Diana (Health and Society, 2024)
This article explores the relationship between emotional dependence, narcissism, social behaviors, and gender inequality. By reviewing the scientific literature, we examine how these factors interrelate and impact social dynamics and individual experiences. Emotional dependence and narcissism are addressed as psychological factors that influence social behaviors and perpetuate gender inequality.